2007
DOI: 10.1177/1742395307081504
|View full text |Cite
|
Sign up to set email alerts
|

Multiple chronic diseases and quality of life: patterns emerging from a large national sample, Australia

Abstract: Multiple chronic diseases were found to have a considerable negative impact on quality of life, not only in terms of how people felt about their lives generally, but also in terms of the extent of their psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 20 publications
12
110
1
1
Order By: Relevance
“…One would expect that patients who report a high satisfaction use their device without serious problems. However, Jannink et al [14] reported a number of serious deficiencies in the performance of AFOs despite the fact that the overall satisfaction was 8.1 (scale [1][2][3][4][5][6][7][8][9][10]. In other words, even a high satisfaction rate may cover up underexposed problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One would expect that patients who report a high satisfaction use their device without serious problems. However, Jannink et al [14] reported a number of serious deficiencies in the performance of AFOs despite the fact that the overall satisfaction was 8.1 (scale [1][2][3][4][5][6][7][8][9][10]. In other words, even a high satisfaction rate may cover up underexposed problems.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of non-use is strongly influenced by the expectations of the patient and his/her environment. Personal characteristics such as age, sex, and living environment also play an important role [9][10]. It is remarkable that many patients choose not to use their device, despite the fact that non-use hinders daily activities and social participation [4,[5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between multiple conditions and poor psychological status has been demonstrated in community studies. 138 Studies focusing on those patients eligible for palliative forms of care are limited to the relationship between disease-specific conditions, comorbidities and psychological distress. The development of new comorbidities is associated with readmission of palliative care patients.…”
Section: Patient Symptom Burdenmentioning
confidence: 99%
“…Evidences from both developed and developing countries show that older people are at much higher risk of multiple co-morbidities (Gijsen et al, 2001;Khanam et al, 2011;Salisbury, Johnson, Purdy, Valderas, & Montgomery, 2011;Salive, 2013;van den Akker, Buntinx, Metsemakers, Roos, & Knottnerus, 1998;Walker, 2007). Multiple morbidities have been proven to be directly associated with adverse health outcomes such as reduced physical functions (Fried, Bandeen-Roche, Kasper, & Guralnik, 1999;Kadam & Croft, 2007), reduced quality of life (Fortin et al, 2004), poor selfrated health (Galenkamp, Braam, Huisman, & Deeg, 2011), and mortality (Hoeymans, Feskens, Kromhout, & van den Bos, 1999).…”
Section: Introductionmentioning
confidence: 99%